Impact of Prediabetes and Type-2 Diabetes on Outcomes in Patients with COVID-19 - Jasbir Makker; Haozhe Sun; Harish Patel; Nikhitha Mantri; Maleeha Zahid; Sudharsan Gongati; Sneha Galiveeti; Sharon W. Renner; Sridhar Chilimuri (International Journal of Endocrinology)
Introduction. The true impact of prediabetes and type-2 diabetes in patients with COVID-19 remains unknown, with studies thus far providing conflicting evidence. Methods. This is a single-center retrospective observational study involving 843 hospitalized patients with SARS-CoV-2 infection. Primary outcomes, mortality, and mechanical ventilation use were compared among the three groups: control, prediabetes, and type-2 diabetes. Binomial regression analysis was used to determine predictors of mortality and mechanical ventilation requirement. Results. Age was a significant predictor of mortality. On stratifying our patients based on their age, older patients aged 55 years and above had no difference in mortality or mechanical ventilation requirement among the three groups of control, prediabetes, and type-2 diabetes. However, among the younger population aged less than 55 years, patients with type-2 diabetes had significantly higher mortality as compared with patients in control and prediabetes groups (27% vs 12.5% vs 9%, p 0.025). Additionally, newly diagnosed type-2 diabetes patients demonstrated lower mortality rate in comparison to previously known type-2 diabetes patients (18% vs 40%, p 0.005). Outcomes in the prediabetes group were similar to that in the control group. Admission hyperglycemia was associated with higher mortality regardless of diabetes status. Conclusion. In older patients aged 55 years and above, status of type-2 diabetes does not influence their mortality. However, in younger patients aged less than 55 years, the presence of type-2 diabetes is an important driver of mortality. Newly diagnosed type-2 diabetes, in comparison with previously diagnosed type-2 diabetes, may have better survival. Presence of prediabetes did not affect outcomes in patients with COVID-19 infection.